The Impact of Corporate News on Stock Prices: Evidence from the Russian Stock Market - Liudmila Ruzhanskaya; Valentin Voytenkov; Alina Urazbaeva; Lilit Danielian (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2022)
In the face of complex sanctions, Russian companies are looking for new mechanisms to ensure sustainability. An overcrowded corporate news backdrop could be the source for a significant decline in a company’s market value or growth. Given the importance of information disclosure and corporate news for investors’ expectations, we estimate the effect that four types of corporate news (Official publication of financial results for the quarters and for the year; M&A; Appointment of new persons; Dividend policy) impose on shares of three Russian companies in different industries: the financial, energy and high-tech sectors. In order to reflect corporate news’ influence, we developed an index of corporate news for the companies concerned utilizing daily data ranging 2015–2021. By applying a vector error-correction model, we demonstrate that corporate news and corporate equities are related over the long run. Short-run results obtained with the Granger test suggest no evidence of causality. At the second stage, we construct impulse response functions that affirm the effect of corporate news on stocks. Corporate news has a high and positive effect on stock prices in the high tech and energy sectors, while the financial sector reacts in a mixed manner to corporate news, and the effect is weak. Obtained results serve as the basis for practical recommendations to individual and institutional investors, as well as to companies for market value management.